A experiência de adoecimento de uma trabalhadora de enfermagem de uma instituição hospitalar de Cuiabá-MT - Cunha, Carla Rafaela Teixeira (2011)
The health work is related to the varied activities, this diversity points to the importance of studies that focus on this type of work and its relation with the illness of the workers. In this context, the hospital work provides a greater vulnerability of workers to some forms of chronic illness. The studies on the chronic illness of such workers, as well as the meanings attributed to them are relevant, because they will be able to provide empirical and theoretical foundations for the creation of actions and effective policies for the protection of worker health/nursing. In this research the focus will be based on the experience of illness of a technique in nursing in license for health treatment due to musculoskeletal disorders by showing their trajectory of search for care and also of their rights. Our objective was to understand the experience of illness and medical leave for a technique of nursing in a hospital institution of Cuiaba-MT. Qualitative case study in the biographical perspective, supported on the concepts of “illness experience” associated with the work of hospital nursing and in their narratives to give meaning to the illness. The data were collected by in-depth interviews and analyzed thematically, showing three categories. The first category was called : The life of work before the illness, with the subcategory: “I was working gone even” , which evidence the importance of recognizing the participant in the study as the subject of his experience of illness, valuing their interpretations, experiences and the meaning that the work had for her illness. The second category was entitled to “The illness experience and search for care”, showing the therapeutic itinerary in search for care, and the experience of illness of nursing workers goes beyond what is considered by health professionals and institutional managers, and the subcategory “We think twice before getting sick” showing that to have the right of distance by health leave during their treatment, the worker and her family has followed an institutional trajectory, mainly to ensure that its right of distance. This institutional trajectory hasn‟t always met the needs of the worker in a moment of illness. The third category was called: life after the illness with the subcategory: “I considered a new chance, I think that why I had to remake my ideas”. In this category, the narratives portray that the passage through the experience of the illness is characterized as a new opportunity to direct her life, leading to biographical rupture, considering now his life in before and after the illness. The study points to the need for expansion of our conception of illness, through the perception of those who experience the illness at work of hospital nursing. We observed that the field of health worker is dynamic and complex, requiring to the rulers and health professionals actions to guarantee the integral care to this population, analyzing that the illness is also reflected in this dynamic of the work, so we propose new approaches to the understanding the process.